Attaining low uncertainties in measurements with RF signal generators and analyzers - Beuster, Niklas; Raschke, Florian; Ihlow, Alexander; Andrich, Carsten; Del Galdo, Giovanni (I2MTC 2017 - 2017 IEEE International Instrumentation and Measurement Technology Conference, Proceedings, 2017)
In this paper, practical investigations of level accuracy and uncertainties using a Rohde & Schwarz signal generator (R&S SMB-B140) and spectrum analyzer (R&S FSV40) are performed up to 30GHz. We show that it is possible to measure frequency responses of DUTs with uncertainties below ±0.05dB up to 30 GHz instead of ±0.5.1.5dB using auto settings, standard setup, or relying on datasheets. The level linearity of instruments with integrated step attenuators is shown to be improved to ±0.03dB instead of ±0.3.1dB by using a special 'hybrid' procedure. Furthermore, it is shown how computer aided measurements procedures should be programmed with these instruments to attain low deviations between measurements.
CRIS-Team Scopus Importer:2025-11-10
Keywords: Calibration; Instruments; RF measurements